Implementation of a Problem-Based Learning (PBL) Model Assisted By Zoom Cloud Meeting in Improving High School Students’ Critical Thinking Skills and Learning Motivation on the Concept of Environmental Pollution - Nurjanah Handayani; Abdul Muizz; Wahidin Wahidin; Sofyan Nur (Publikasiku, 2022)
This study aims to determine the effectiveness of the problem-based learning (PBL) model in improving the critical thinking skills and learning motivation of 10th grade senior high school students through the biology-based learning of environmental concepts and pollution, especially water and soil pollution. This study also aims to determine students' responses to the problem-based learning model. A quasi-experiment with a control group before and after the test is used to conduct the research. This research was done over the course of four meetings. The population of this study consists of all 10th-grade senior high school students, with the following characteristics: the first 10th-grade senior high school students are an experimental class implementing PBL with Zoom Cloud Meeting, and the second 10th-grade senior high school students are a control class with a scientific approach learning model. The N-Gain test was used to measure critical thinking skills before and after learning, as well as the level of motivation at the end of learning, to collect data for this study. The findings showed that: 1) The PBL model was implemented successfully, with a score of 95%, using Zoom cloud meetings. 2) When compared to the 5M models, the implementation of learning using the PBL model through Zoom Cloud Meetings improved students' critical thinking skills. The N-Gain test results were within the middle range, precisely 0.51. 3) Using Zoom cloud meetings to apply the PBL approach has no meaningful effect on increasing students' learning motivation. 4) Students were highly enthusiastic about studying the PBL methodology using Zoom cloud sessions